Mathematics Teachers' Attitudes Towards Using the Solving Mathematical Problems Method in the Basic Education Stage A Field Study on Fourth Grade Teachers in Lattakia city (Journal of Hama University, 2024)
The current research aimed to study the attitudes of mathematics teachers towards using the mathematical problem solving in mathematics, and to investigate the impact of the following variables (numbers of experience years, academic qualification, training courses) on their attitudes towards using the solving mathematical problems method), and to achieve the objective of the research, the researcher applied a questionnaire to find out the attitudes of teachers towards this method, and the research sample included (164) teachers for the academic year 2023/2022, and the descriptive approach was used.The research concluded that the attitudes of mathematics teachers towards using the solving mathematical problems method came to a high degree, and the results showed that there were no statistically significant differences between the attitudes of teachers towards using the solving mathematical problems in mathematics method according to the variable numbers of experience years, and the existence of statistically significant differences according to the variables (scientific qualification in favor of postgraduate, and training courses for those who followed training courses).
Keywords: Attitudes, Mathematics Teachers, Method of Solving Mathematical Problems, the Fourth Grade.